2017
DOI: 10.1097/mco.0000000000000395
|View full text |Cite
|
Sign up to set email alerts
|

A requiem for BMI in the clinical setting

Abstract: BMI, as the traditional tool for assessing malnutrition and obesity, is not appropriate to accurately differentiate between important body weight components and therefore should not be used for making clinically important decisions at the individual patient level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
128
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 166 publications
(139 citation statements)
references
References 49 publications
4
128
0
7
Order By: Relevance
“…We are aware of the limitations of using BMI to estimate body fat and lean mass at the individual level. It is possible that some of the included patients had a higher lean body mass composition but were not malnourished [41]. However, we have other clinical data in addition to the BMI values that support the claim that the vast majority of the patients included in this study were undernourished: 33.9% of the patients had a history of prior weight loss, 79.2% of the patients had temporal muscle wasting, and 79.8% of the patients had pre-existing illness, all of which corroborate the diagnosis of malnourishment in the patients evaluated in our study.…”
Section: Patients Characteristics and Outcomesmentioning
confidence: 99%
“…We are aware of the limitations of using BMI to estimate body fat and lean mass at the individual level. It is possible that some of the included patients had a higher lean body mass composition but were not malnourished [41]. However, we have other clinical data in addition to the BMI values that support the claim that the vast majority of the patients included in this study were undernourished: 33.9% of the patients had a history of prior weight loss, 79.2% of the patients had temporal muscle wasting, and 79.8% of the patients had pre-existing illness, all of which corroborate the diagnosis of malnourishment in the patients evaluated in our study.…”
Section: Patients Characteristics and Outcomesmentioning
confidence: 99%
“…In the past, weight loss and body mass index (BMI) have been used as an indicator of such nutritional decline and poor prognosis . However, because of the increased number of patients presenting in an overweight or obese state in the developed world, the use of simple weight loss and BMI as a prognostic indicator has been questioned . The ability to use routine computed tomography (CT) scans to measure body composition, in particular skeletal muscle, has resulted in a marked increase in interest in using skeletal muscle index (SMI) and skeletal muscle density (SMD) to predict outcomes in patients with cancer, particularly in CRC …”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, because of the increased number of patients presenting in an overweight or obese state in the developed world, the use of simple weight loss and BMI as a prognostic indicator has been questioned. [4][5][6][7] The ability to use routine computed tomography (CT) scans to measure body composition, in particular skeletal muscle, has resulted in a marked increase in interest in using skeletal muscle index (SMI) and skeletal muscle density (SMD) to predict outcomes in patients with cancer, particularly in CRC. 8 There is evidence supporting a disproportionate loss of skeletal muscle tissue to be an independent prognostic factor for both cancer specific and overall survival in patients with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…It is especially challenging to predict the degree of muscularity in overweight and obese patients because it can vary widely . Body mass index (BMI) categories are not able to predict muscularity in various population .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Body mass index (BMI) categories are not able to predict muscularity in various population. 17 Although studies had shown that higher BMI confers survival benefits in the critically ill patient population, 18 others have found that LM is associated with poorer outcome among overweight or obese patietns. 19,20 As Malaysia has the highest prevalence of overweight (men 43.8%, women 48.6%) and obesity (men 11.4%, women 16.7%) in the South East Asia region, the proportion of obese patients with LM is worthwhile to be explored.…”
Section: Introductionmentioning
confidence: 99%